Process strategies to reduce cellulase enzyme loading for renewable sugar production in biorefineries - Reis, Cristiano E. Rodrigues (2023)
Second-generation (2G) sugar is the principal building block in biorefineries producing sustainable fuels, green chemicals, and materials. Its production involves a pre-treatment strategy, which can remove either hemicellulose or lignin, followed by a cellulase cocktail-mediated hydrolysis of pre-treated biomass applying numerous modifications. The high production cost of sugar from biomass using high-solid loadings with the desired purity is the important limiting factor for their economic conversion into bio-renewables. Pre-treatment and cellulase-mediated enzymatic hydrolysis of recalcitrant biomass are among the major technical and economic impediments to the overall success of biorefineries. Critical parameters such as the high amount of cellulase required for biomass hydrolysis, high cellulase cost, unproductive binding of cellulase to lignin, inhibitive reactions, and lower substrate applicability directly influence the recovery of sugar at a competitive price. Understanding the interaction of the relationship of the enzymes and substrates with the interactions of the reducing cellulase amount and effective hydrolysis rate should be positioned for the recovery of 2G sugar at a competitive price. Thus, effective strategies are needed to minimize cellulase dosage to overcome the cost of the enzyme. Further, on-site enzyme production, the addition of pre-treated biomass in fed-batch mode, and the washing of pre-treated biomass can play a pivotal role in the economic production of 2G sugar. This review provides a comprehensive analysis of the specific strategies such as applying extraneous proteins and additives, enzyme recycling, and effect of washing pre-treated biomass on 2G sugar production at a large scales in lignocellulose biorefineries.